PERAN KEPALA SEKOLAH PEREMPUAN DALAM UPAYA PENINGKATAN MUTU PENDIDIKAN DI SEKOLAH DASAR MUHAMMADIYAH 01 PEKANBARU - Tuti Andriani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This article discusses the role of female school principals in efforts to improve the quality of education in Muhammadiyah Elementary School 01 Pekanbaru, which uses descriptive qualitative methods. The key informants were the Principal of the Muhammadiyah Elementary School 01 Pekanbaru and the supporting informants were teachers, foundation administrators, students, parents, and the surrounding community. Data collection techniques using interviews and documentation. Data analysis techniques through the stages of data reduction, data display, conclusion drawing and verification. The research findings show that female school principals have the ability to improve the quality of education by acting as administrators, supervisors, innovators and motivators. Supporting factors are: (1) friendly and gentle nature; (2) the assertiveness of women; (3) management knowledge; (4) willing to sacrifice both in terms of material and time; and (5) collective and collegial leadership. While the inhibiting factors are: (1) it is still difficult for a female leader to hide/ control her emotions; (2) physical condition which is weak or vulnerable to disease, is one of the obstacles to the role of women's leadership; and (3) the difficulty of collaborating with foundations, so that it impedes women's leadership a bit.